Product Marketing Strategy Muamalat Din (Digital Islamic Network) at PT. Bank Muamalat Indonesia Tbk - Kadariah, Siti; binti Noor Azman, Fathi Khalilah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The purpose of this study is to determine product marketing strategies using Muamalat DIN (Digital Islamic Network) at PT. Bank Muamalat Indonesia Tbk KCU Padangsidimpuan. to find out the obstacles faced by Bank Muamalat Indonesia Tbk KCU Padangsidimpuan in product marketing strategies using Muamalat DIN (Digital Islamic Network). This research is qualitative research with descriptive methods. The subjects of the study were 2 employees and 4 customers. Data collection techniques are obtained from observation, interviews, documentation. While data analysis techniques include data reduction, data presentation, and conclusions. While the technique of checking the validity of data uses triangulation.The results showed that the product marketing strategy uses Muamalat DIN (Digital Islamic Network) at PT. Bank Muamalat Indonesia Tbk KCU Padangsidimpuan by visiting foundations and the community or prospective customers by conducting direct socialization to introduce products and services available at Bank Muamalat Indonesia Tbk KCU Pangsidimpaun. The obstacle in carrying out marketing strategies from internal factors is the lack of branch offices and crew in marketing strategies while external factors lack customer interest in using it due to age.